2016
DOI: 10.1016/j.celrep.2016.09.037
|View full text |Cite
|
Sign up to set email alerts
|

ZMYND8 Co-localizes with NuRD on Target Genes and Regulates Poly(ADP-Ribose)-Dependent Recruitment of GATAD2A/NuRD to Sites of DNA Damage

Abstract: NuRD (nucleosome remodeling and histone deacetylase) is a versatile multi-protein complex with roles in transcription regulation and the DNA damage response. Here, we show that ZMYND8 bridges NuRD to a number of putative DNA-binding zinc finger proteins. The MYND domain of ZMYND8 directly interacts with PPPLΦ motifs in the NuRD subunit GATAD2A. Both GATAD2A and GATAD2B exclusively form homodimers and define mutually exclusive NuRD subcomplexes. ZMYND8 and NuRD share a large number of genome-wide binding sites,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
142
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(155 citation statements)
references
References 48 publications
12
142
1
Order By: Relevance
“…Each protein robustly co‐purified with all known NuRD component proteins, including each of the MTA proteins, confirming that MTA proteins are not mutually exclusive within NuRD in ES cells (Fig C). In addition to NuRD components, each of the MTA proteins co‐purified with Wdr5 as well as a number of zinc finger proteins, most of which had previously been identified as NuRD‐interacting proteins (Bode et al , ; Spruijt et al , ; Ee et al , ; Matsuura et al , ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each protein robustly co‐purified with all known NuRD component proteins, including each of the MTA proteins, confirming that MTA proteins are not mutually exclusive within NuRD in ES cells (Fig C). In addition to NuRD components, each of the MTA proteins co‐purified with Wdr5 as well as a number of zinc finger proteins, most of which had previously been identified as NuRD‐interacting proteins (Bode et al , ; Spruijt et al , ; Ee et al , ; Matsuura et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…Nucleosome Remodelling and Deacetylation is comprised of two enzymatically and biochemically distinct subcomplexes: a chromatin remodelling and a deacetylase subcomplex. The chromatin remodelling subcomplex contains a nucleosome remodelling ATPase protein (Chd3/4/5) along with one of the zinc finger proteins Gatad2a/b and the Doc1/Cdk2ap1 protein, while the deacetylase subcomplex contains class I histone deacetylase proteins Hdac1/2, the histone chaperones Rbbp4/7, the Metastasis Tumour Antigen family of proteins, Mta1, Mta2 and Mta3 and, in pluripotent cells, the zinc finger proteins Sall1/4 (Lauberth & Rauchman, ; Allen et al , ; Kloet et al , ; Bode et al , ; Low et al , ; Miller et al , ; Spruijt et al , ; Zhang et al , ). These two subcomplexes are bridged by Mbd2/3, creating intact NuRD (Fig A).…”
Section: Introductionmentioning
confidence: 99%
“…The MYND domain of ZMYND8 is responsible for its interactions with the NuRD complex, notably the core catalytic component CHD4 [54]. Importantly, ZMYND8 has been identified as a new DDR (DNA Damage Response) factor; ZMYND8 recruits CHD4 to the sites of DNA damage and represses transcription and facilitates DNA repair by homologous recombination [54, 63]. Thus, ZMYND8 is implicated in both transcriptional activation and silencing, as well as DNA damage in a context-specific manner.…”
Section: Discussionmentioning
confidence: 99%
“…However, no structural data at any resolution have been presented for the intact complex. The subunit stoichiometry is also uncertain; recent studies using label-free mass spectrometry (33)(34)(35)(36)(37)(38) have yielded variable results that are often at odds with the stoichiometries demonstrated in the known subcomplex structures.…”
Section: Ino80mentioning
confidence: 99%
“…Some structural information is available for portions of the NuRD complex ( Figure S1b): (i) HDAC1 forms a 2:2 complex with an N-terminal segment of MTA1 (MTA1 162-335 -the ELM-SANT region) (27); (ii) single particle electron microscopy (SPEM) and X-ray crystallography data show that two copies of RBBP4 can bind the C-terminal portion of MTA1 (28-30); (iii) MBD2 and GATAD2A form a heterodimeric coiled-coil (24, 31); and (iv) a cryo-EM structure has been determined for the complex between the catalytic domain of CHD4 and a nucleosome particle (32).However, no structural data at any resolution have been presented for the intact complex. The subunit stoichiometry is also uncertain; recent studies using label-free mass spectrometry (33)(34)(35)(36)(37)(38) have yielded variable results that are often at odds with the stoichiometries demonstrated in the known subcomplex structures.The mechanisms by which NuRD selects target sites are also poorly understood. Transcriptional regulators such as FOG1 (22,39) and BCL11A (40,41) can bind to NuRD via the RBBP subunits but this mechanism is likely to account for only a small proportion of NuRD-genome interactions.Recently, we demonstrated that the chromatin-binding protein PWWP2A, which can selectively recognize H2A.Z-containing nucleosomes (42,43), interacts robustly with the MTA, HDAC and RBBP subunits of NuRD.…”
mentioning
confidence: 99%